Peran Tenaga Kefarmasian Dalam Pelayanan Penyakit Faringitis Di Apotek Wilayah X Propinsi Banten - Yardi Saibi; Suci Ahda Novitri; Erza Agustia (Pharmaceutical and Biomedical Sciences Journal (PBSJ), 2025)
Pharyngitis, or sore throat inflammation, is a disease generally caused by a virus and can heal on its own within a few days. However, symptoms such as pain when swallowing can cause discomfort for patients. Patients often come to the pharmacy to get medication without first consulting a doctor. The purpose of this study was to determine the role of pharmacists in region X in Banten province in providing pharmaceutical services to patients who come with complaints of sore throat. This study is a cross-sectional study using a survey method. Data collection methods were carried out using two methods, the first is participatory observation where researchers and observers acted as patients visiting selected pharmacies by conveying the complaints in question based on the scenario created. The second method was conducting interviews with pharmaceutical personnel at pharmacies in one of the selected areas who met the specified inclusion and exclusion criteria. The results of the study showed that in the patient simulation method: methyl prednisolone was the most frequently prescribed drug (52%), followed by lozenges containing dequalinium chloride (32%), the most frequently asked questions by pharmaceutical personnel when assessing patients were the symptoms experienced (63%) followed by the patient's age (53%). Meanwhile, in the interview method, lozenges containing dequalinium chloride were the most frequently prescribed medication (78%), followed by methylprednisolone (46%). The most frequently asked questions during patient assessment were the patient's age (98%), followed by the duration of symptoms experienced (96%). The drug's usage information was the most frequently conveyed information in both methods. The patient assessment process and drug information provided to patients in the interview method were better than in the simulated patient method. In general, pharmaceutical services provided by pharmacists to patients with sore throat problems are still not optimal and need to be improved